Accurate evaluation of mode of delivery and labor progression with angle of progression: a prospective cross-sectional - Huong Lam Le; Huy Vu Quoc Nguyen; Tam Minh Le; Lam Hoang Vo (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To determine the validity of the angle of progression (AoP) in predicting delivery mode among women in the second stage of labor. Designs: This prospective cohort study was conducted at the Obstetrics and Gynecology unit (OBGYN) of two hospitals in Vietnam. Transperineal ultrasound was performed for each woman to measure the progression angle in the second phase of labor. data were collected from Participants: A total of 725 women with singleton pregnancies with cephalic presentation at term Methods: Transperineal ultrasound was used to measure the angle of progression in the second labor phase and to identify the delivery method. Results: The rate of vaginal birth in women with an AoP ≥ 120° on transperineal ultrasound was 70.2%. The optimal cutoff point of AOP ≥122° with sensitivity and specificity for vaginal birth were 87.8% and 80.7%, respectively the area under the ROC curve of 0.887 (p<0.0001). The study's sample size was restricted owing to deficiencies in resources and time. Conclusion: The likelihood of achieving spontaneous vaginal delivery can be predicted by the angle of progression measured with transperineal intrapartum ultrasonography during the second stage of labor in women.